Editorial - R. Hiremath, Shobha Rani. (Indian Journal of Pharmacy Practice)
This year we have lost Senior Professor Dr.B.D.Miglani, Advisory Board Member of the Indian Journal of Pharmacy Practice who is popularly known as the “Father of Hospital Phamacy” in India. Dr.Miglani founded Indian Hospital Pharmacists’s Association way back in 1963 and laid a foundation and held positions of General Secretary (1964-1971) , President (1972-1973) and Patron of IHP Association. He showed keen interest in the development of Hospital Pharmacy in India. Dr.Miglani was the Founder Editor of the Indian Journal of Hospital Pharmacy (1964-2007).